(3MbGFb GdESJTgGOs - (3GdWZQGFj , GdMSjf Hf Ydj Hf eMeO Hf YHO GdUeO GdCUHgGfj GdWZQGfj, eDjO GdOjf CHh ESeGYjd,J (B513 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI(B: (3CSYOcGddg HWGYJg hLYdc ef GdaGFRjf HQMeJg s
(3BNQgG (B:s
(3Je cJGH MbGFb GdEJTgGO Hbhd GdMcje GdLhGO s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B340s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B247 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B439 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B37 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WHjYI (B170) s
Keywords: (3GdcjejGA h GdWHjYjGJs